Foreign Direct Investment in Nepal - Neupane, Maheshwor (Social Inquiry: Journal of Social Science Research, 2020)
This article is about the relationship between Foreign Direct Investment(FDI) and Gross Domestic Product (GDP). It explores the FDI’s linkage with the national income. The data for the study comprised different factors that have a direct linkage with the national economy and its impact. This article is based on the FDI in various sectors in terms of the number of projects, employment created, and the amount invested. It is based on secondary data. The study revealed that FDI sometimes has an independent influence on the economy of the country. A fresh finding of this article is that the contribution of FDI in capital formation and employment is not significant in the Nepalese economy, eventually making less contribution to the GDP of the Nepalese economy. It also revealed that FDI comprises new technologies, management techniques, finance and market access for the production and movement of goods and services. So, Nepal should adopt policies to attract more FDI and implement accordingly.